PENGATUR KETINGGIAN AIR OTOMATIS - Prawiroredjo, Kiki; Susantio, Ignatius Melvin (Jurnal Teknik Elektro, 2010)
The Automatic Water Level Control is a prototype circuit that controls the availability of water in a tank. The water tank has five water levels to control the pump work. The water level control system consists of two water containers, one for the water source container and the other for the water reservoir and two water pumps. The circuit consists of an infrared system, two relays to activate the water pumps and a 2x16 Liquid sensor to detect the water level, a microcontroller Atmega 8535(L) to control all the circuit Crystal Display (LCD) to display the water level in the tank reservoir and the pump condition. After the water level control circuit has been built and tested, it is known that at the minimum level position that is 30 cm between sensor and the float, the output voltage of the infrared sensor is 0,85 volt and the microcontroller will turn on both the water pumps. At the maximum level position that is 11.5 cm between sensor and the float, the output voltage of the infrared sensor is 2,17 volt and the microcontroller will turn off both of the water pumps. Keywords: Water level control, infrared sensor, Microcontroller, LCD